Remedy for Unproductive Researches and Disintegrated Information in Islamic Finance: ‘Riba Information Queries Digital Portal’ - TAHREEM khan (Global Review of Islamic Economics and Business, 2017)
Abstract: Islamic finance industry evolution and development has been a central concern to scholars, researchers, and managers alike. However for last few years, academia and practitioners have indicated on a serious note that the success and growth of Islamic finance is getting affected because of lack of integration and collaborative approach between different institutions and key actors. Fragmentation plagues the thought process thus saps research productivity, it further create deadlock in research innovation, and makes it hard to be responsive according to the industry and customer needs.  In that case, it is essential to find an answer: How a valuable and impactful platform can be designed which can add knowledge to individuals, bankers and society aswell? Realizing the challenge of fragmented information and disconnected issues in Islamic finance sector, this research attempt to propose a solution which can assist Islamic bankers, Islamic finance education providers, shariah scholars, students and researchers in gathering information and conducting more useful and productive research.